The impact of jangari reservoir tourism on environmental pollution - Arfiyana Destaria Tarmizi; Hertien Koosbandiah Surtikanti (Asian Journal of Toxicology, Environmental, and Occupational Health, 2023)
The purpose of this research is to learn information about the effects of Jangari reservoir tourism On The Environmental Pollution Surrounding Bobojong Village. This study is conducted on the Jangari Reservoir Located In Bobojong Village, Mande District, Cianjur, West Java. Samples in the study include West Java LLASDP employees, tourist conscious groups, bargas owners, Floating Net Cage (KJA) owners, tourists and other communities. The sampling technique used is purposive sampling. This research conducted by observation to the location, ingrate, and interview of the respondents. The questionaire used consisted of 11 questions in the form of multiple choice and stuffing. The data of further research is analysed in a qualitative descriptive way that aimed at describing the quality of the findings based on the study of the references used. The result of this research shows that even though there is not much visible environmental pollution, indications of environmental pollution are already visible, marked by the presence of piles of garbage at several points, styrofoam waste in the waters of the Jangari Reservoir, boat traffic activity in the waters of the Jangari Reservoir, and water hyacinth growing around it. waters to cover the water surface of the reservoir. Waste management in Jangari Reservoir does not carry out 3R (Reuse, Reduce, Recycle), waste management has involved local communities and the government but the implementation has not been maximized because it is not carried out routinely.